2018
DOI: 10.20515/otd.379555
|View full text |Cite
|
Sign up to set email alerts
|

Yaşlılık Döneminde Ağaçtan Düşmeye Bağlı Ölümlerin Değerlendirilmesi

Abstract: Bu çalışmada Eskişehir ilinde meydana gelen, yaşlılık dönemi ağaçtan düşmeye bağlı ölüm olgularının incelenmesi ve adli tıp değerlendirilmesi amaçlanmıştır. İlimizde bu konu ile ilgili yapılan bir çalışma bulunmamaktadır. Eskişehir'de 1997 ile 2016 yılları arasındaki 20 yıllık dönemde ağaçtan düşmeye bağlı ölen 65 yaş üstü 26 olgu retrospektif olarak değerlendirilmiştir. Olguların yaş, cinsiyet, olay yerine ait bulgular ve ölene ait soruşturma bilgileri yönünden değerlendirilmiştir. 20 yıllık dönmede ilimizde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…4 The elderly population is more susceptible to accidents due to balance and coordination problems and diminished sensory functions. 18 In this study, it was found that 38.8% of individuals over 65 years of age visited the emergency department due to falling from a height. Gündüz and Koçaşlı (2017) 4 reported a 16.4% incidence of fall cases among patients aged 71 years and older in their one-year follow-up study conducted in the emergency department.…”
Section: Resultsmentioning
confidence: 77%
“…4 The elderly population is more susceptible to accidents due to balance and coordination problems and diminished sensory functions. 18 In this study, it was found that 38.8% of individuals over 65 years of age visited the emergency department due to falling from a height. Gündüz and Koçaşlı (2017) 4 reported a 16.4% incidence of fall cases among patients aged 71 years and older in their one-year follow-up study conducted in the emergency department.…”
Section: Resultsmentioning
confidence: 77%
“…Some tree types are more hazardous than others; these tree types can be determined locally, and measures can be taken to prevent falls from these trees. Previous studies showed that coconut [9], walnut [10], and other trees were the most hazardous types in those study regions. In our region, patients most frequently fell from fig (54.3%) and pear trees (14.3%).…”
mentioning
confidence: 72%